Audit of 100 consecutive basal cell carcinoma specimens at a secondary care center in the UK - Qureshi, Asim; Qureshi, Hannia; Singla, Ritu; Mohammad Shafiq Gill (Journal of the Pakistan Medical Association, 2023)
Objective: To audit basal cell carcinoma resections against standard guidelines. Methods: The retrospective study was done at the Department of Pathology, Sherwood Forest Hospital, Nottinghamshire, United Kingdom, from July 2020 to December 2020 and comprised basal cell carcinoma cases regardless of age and gender. All parameters laid down by the Royal College of Pathologists were matched with the data. Also, incompletely resected specimens were separated, and reasons for incomplete resection were taken into account, and compared with the British Association of Dermatologists 2018 guidelines. Results: Of the 100 consecutive cases, 67(67%) were nodular and nodulocystic, 8(8%) were superficial multifocal, 7(7%) each were infiltrative and mixed nodular and infiltrative, 6(6%) were mixed nodular and superficial, and 5(5%) were mixed superficial and infiltrative. All 100(100%) pathology reports contained the mandatory information set by the Royal College of Pathologists. There were 7(7%) incompletely excised cases. The rate of incomplete excision was also within the acceptable range defined by the British Association of Dermatologists 2018 guidelines. Conclusion: All basal cell carcinoma resections were in line with the standard guidelines. Key Words: Basal cell carcinoma, Audit, RCPath.